Licochalcone A inhibits proliferation and promotes apoptosis of colon cancer cell by targeting programmed cell death-ligand 1 via the NF-κB and Ras/Raf/MEK pathways. (12th June 2021) - Liu, Xueshuang; Xing, Yue; Li, Mingyue; Zhang, Zhihong; Wang, Jingying; Ri, MyongHak; Jin, Chenghua; Xu, Guanghua; Piao, Lianxun; Jin, Honglan; Zuo, Hongxiang; Ma, Juan; et al.
Abstract: Ethnopharmacological relevance: Glycyrrhiza glabra L., a traditional medicinal, has a history of thousands of years. It is widely used in clinic and has been listed in Chinese Pharmacopoeia. Licochalcone A is a phenolic chalcone compound and a characteristic chalcone of Glycyrrhiza glabra L. It has many pharmacological activities, such as anti-cancer, anti-inflammatory, anti-viral and anti-angiogenic activities. Aim of the study: In this study, we explored the anti-tumor activity and potential mechanism of licochalcone A in vitro and in vivo. Materials and methods: In vitro, the mechanism of licochalcone A at inhibiting PD-L1 expression was investigated by molecular docking, western blotting, RT-PCR, flow cytometry, immunofluorescence and immunoprecipitation assays. The co-culture model of T cells and tumor cells was used to detect the activity of cytotoxic T lymphocytes. Colony formation, EdU labelling and apoptosis assays were used to detect changes in cellular proliferation and apoptosis. In vivo, anti-tumor activity of licochalcone A was assessed in a xenograft model of HCT116 cells. Results: In the present study, we found that licochalcone A suppressed the expression of programmed cell death ligand-1 (PD-L1), which plays a key role in regulating the immune response. In addition, licochalcone A inhibited the expressions of p65 and Ras. Immunoprecipitation experiment showed that licochalcone A suppressed the expression of PD-L1 by blocking the interaction between p65 and Ras. In the co-culture model of T cells and tumor cells, licochalcone A pretreatment enhanced the activity of cytotoxic T lymphocytes and restored the ability to kill tumor cells. In addition, we showed that licochalcone A inhibited cell proliferation and promoted cell apoptosis by targeting PD-L1. In vivo xenograft assay confirmed that licochalcone A inhibited the growth of tumor xenografts. Conclusion: In general, these results reveal the previously unknown properties of licochalcone A and provide new insights into the anticancer mechanism of this compound. Graphical abstract: Image 1 Highlights: Licochalcone A inhibits NF-κB and Ras/Raf/MEK signaling pathways activation. Licochalcone A inhibits PD-L1 expression by blocking the p65 and Ras interaction. Licochalcone A inhibits cell proliferation and promotes cell apoptosis by PD-L1. Licochalcone A restores the tumor-killing activity of T-cells by PD-L1. Licochalcone A inhibits the growth of HCT116 cells in a xenograft tumor model.